Evolution of the Igneous Rocks : Fiftieth Anniversary Perspectives - Yoder, Hatten Schuyler (Book collections on Project MUSE., 2015)
The Evolution of the Igneous Rocks, by N.L. Bowen, appeared in 1928 and had a profound influence on later generations of petrologists. Drawing on his series of lectures at Princeton University in the spring of 1927, Dr. Bowen identified, outlined, and applied the principles of physical chemistry relevant to petrological processes. Whereas the major petrochemical questions he discussed are still relevant today, the answers appear to change with time. The purpose of the present volume is to provide an updated view of those questions, in the light of almost fifty years of accumulated observatio.